Properties of finger joint from the Acacia species, Shorea species and Vatica species / Mohd Isma Aliff Mat Sani - Mat Sani, Mohd Isma Aliff (2007)
In this study, three different of wood species is uses to determined the properties of finger joint for Acacia spp, Shorea spp and Vatica spp. All the species is coming from the UiTM Wood industry Factory. To make finger joint, first step is get the raw material, secondly cut the wood into requirement sizes, after that dry the wood to get a requirements moisture contents. After this process, finger joint will be making. Finger joint will be glued and after this process, clamping process is followed. We use the manual clamping. Lastly, the finger joint is sanding to get a smooth surface. For the result, we found the Vatica spp properties are suitable to make finger joint.